STATE POLICY OF ECONOMIC SECURITY OF AGRICULTURE - S. Kal’nyi (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper examines theoretical background, problems and goals of agriculture state regulation in order to ensure economic security in the context of sustainable economic development.